Türkiye in the MENA Region A Foreign Policy Reset - Talbot, Valeria (ISPI Publications, 2023)
In recent years, Türkiye's foreign policy has been driven by efforts to reset relations with regional competitors in the Middle East and North Africa (MENA) region. Against a backdrop of disruption caused by the Covid-19 pandemic and the Russian invasion of Ukraine, as well as the redefinition of the US role in the region, Ankara's renewed diplomatic activism has been guided by the willingness to break from regional isolation, as well as the need to relieve Türkiye's deteriorating economy. How did Türkiye ditch its ideological approach in the wake of the 2011 Arab uprisings to adopt a more pragmatic stance? And how is the process of rapprochement with other key actors in the MENA region playing out - namely Gulf monarchies, Israel and Egypt?